2021
DOI: 10.15835/nbha49212314
|View full text |Cite
|
Sign up to set email alerts
|

Light-emitting diode spectra modify nutritional status, physiological response, and secondary metabolites in Ficus hirta and Alpinia oxyphylla

Abstract: Lighting spectrum is one of the key factors that determine biomass production and secondary-metabolism accumulation in medicinal plants under artificial cultivation conditions. Ficus hirta and Alpinia oxyphylla seedlings were cultured with blue (10% red, 10% green, 70% blue), green (20% red, 10% green, 30% blue), and red-enriched (30% red, 10% green, 20% blue) lights in a wide bandwidth of 400-700 nm. F. hirta seedlings had lower diameter, fine root length, leaf area, biomass, shoot nutrient (N) and phosphorus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 42 publications
1
15
0
Order By: Relevance
“…Therefore, the spectrum of low-intensity light is an important determinant of medicinal bioactive compounds in shade-tolerant plants. For example, both total flavonoid and saponin concentrations were found to be higher in Alpinia oxyphylla plants subjected to a red-light spectrum (30% red, 10%, green, 20% blue) [ 25 ]. Allium victorialis plants had higher concentrations of total flavonoids and saponins when subjected to a green-light spectrum (28% red, 71% green, and 1% blue) [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the spectrum of low-intensity light is an important determinant of medicinal bioactive compounds in shade-tolerant plants. For example, both total flavonoid and saponin concentrations were found to be higher in Alpinia oxyphylla plants subjected to a red-light spectrum (30% red, 10%, green, 20% blue) [ 25 ]. Allium victorialis plants had higher concentrations of total flavonoids and saponins when subjected to a green-light spectrum (28% red, 71% green, and 1% blue) [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, greater fine root morphology in the high-green spectrum in our study did not occur in E . senticosus [ 14 ], Bletilla striata [ 43 ], Ficus hirta , and Alpinia oxyphylla [ 9 ]. All these formally published studies reported a larger fine root system in the spectrum enriched in red light.…”
Section: Discussionmentioning
confidence: 99%
“…senticosus has acclimated to high shading and more green light proportion in the sunlight spectrum [ 44 ]. The plants mentioned were all highly tolerant to shade as well [ 9 , 35 , 43 ]. Juvenile trees, such as Luohan pine and P .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seeds of Bidens Pilosa and Plantago asiatica were obtained from Guiyang Center Nursery (26 C and a relative humidity of 85% [41]. When seeds germinated to the stage when the first pair of cotyledons burst, they were transplanted to pots (top Ø 21 cm, bottom Ø 15.5 cm, height 15.0 cm) filled with washed sands.…”
Section: Plant Materials and Experiments Commencementmentioning
confidence: 99%